THE UTERINE AND FETOPLACENTAL HEMODYNAMICS IN PREGNANT WOMEN WITH PLACENTA PREVIA AND PLACENTA ACCRETA - T. A. Zamanskaya; A. V. Bushtyrev; I. О. Bushtyreva; V. V. Stashkevich; V. V. Antimirova (Акушерство, гинекология и репродукция)
The aim of the study was to analyze the uterine and fetoplacental hemodynamics in pregnant women with placenta abnormalities. Materials and methods. Fifty pregnant women with normal placentation (Group 1), 50 women with placenta previa (Group 2) and 28 women with placenta accreta (Group 3) were examined in this study. The ultrasound examination included the traditional fetometry and an assessment of fetus anatomy and localization of the placenta. In addition, the Doppler ultrasound was used to examine the blood flow in the uterine arteries as well as the umbilical artery and the middle cerebral artery of the fetus. The measurements were performed on the 20-22nd, 30-32nd and 35-36th weeks of gestation.Results. According to the data obtained, the blood flow in the uterine arteries of patients with placenta pervia was much higher as compared with women with normal placental localization. The right uterine artery blood flow indices in the placenta previa cases significantly differed from those in women with placenta accreta. The pulsatility index in the right uterine artery was significantly lower in patients with placenta accreta as compared with the two other groups. The data on fetoplacental hemodynamics indicated differences in the umbilical artery blood flow between women with placenta accreta, placenta previa and normal placental localization on the 20-22nd and 35-36th weeks of gestation. Along with the above findings in the uterine and fetoplacental hemodynamics, the parameters of blood flow in the fetal middle cerebral artery did not differ significantly between the three groups of women at any period of gestation.Conclusion. The conditions of placenta accreta and placenta previa are associated with a decrease in the peripheral vascular resistance in both uterine arteries during all periods of gestation. This conclusion is supported by the lower values of the pulsatility index in these blood vessels in comparison to the values in patients with normal placental localization.